The Effectiveness Of Implementing SBT (Students Behavior Target) Books In Improving The Character Of Student Learning Responsibility - M. Naelul Mubarok; Kama Abdul Hakam; Aceng Kosasih; Momod abdul Somad; Sri Mulya Nurhakiky (International Conference on Elementary Education, 2023)
This study aims to determine the effectiveness of using SBT (Student's Behavior Target) Books in improving character of student learning responsibility. The book is basically a book used as an independent character control book used by students in internalizing the character values taught in the skeolah. By implementing the book, students carry out a series of activities that allow students to stay in controlled activities. Students carry out planning of character target activities, Students plan character target activities, students actualize them and students conduct assessments or measurements on the achievement of the results of internalizing their respective character values, conduct evaluations and relections to see their individual achievements. With this activity book, students can find obstacles or problems in internalizing values, so that in the end they come up with ideas to solve problems that arise independently. This type of research is field research. This type of research is field research. The method used in this study is the experimental method, quantitative data analysis approach, and through pretest and posttest design. The number of samples in this study was 45 students. The results showed that the difference between pretest and posttest value of responsibility scores shows an increased score. Pretest score the responsibility of the student is at a moderate/sufficient level, Posttest score at a high level of responsibility. This means the use of SBT Books proven to increase the value of student learning responsibility. As for the criteria for the effectiveness of the book be in the moderate category.